2014
DOI: 10.5551/jat.25940
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Neutrophil-to-Lymphocyte Ratio in Predicting the Severity of Coronary Artery Disease: A Gensini Score Assessment

Abstract: Aim:The usefulness of the white blood cell (WBC) count and neutrophil-to-lymphocyte ratio (NLR) in predicting the severity of stable coronary artery disease (CAD) has not been sufficiently evaluated, particularly based on strict coronary assessments. The aim of the present study was to investigate the WBC count and NLR in predicting the severity of angiographically proven CAD. Methods: A total of 2,976 CAD patients and 571 non-CAD patients were consecutively enrolled, and the CAD patients were classified into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 34 publications
4
49
1
2
Order By: Relevance
“…Similar to data from previous studies 29) , NLR was significantly higher in UA patients (4.0 2.6) than in SA patients (2.7 1.6, P 0.01) and controls (2.1 0.8, P 0.001), but no significant difference existed between SA and controls (Fig. 1a).…”
Section: Comparison Of Neutrophil -Lymphocyte Ratio (Nlr) In Three Stsupporting
confidence: 81%
See 2 more Smart Citations
“…Similar to data from previous studies 29) , NLR was significantly higher in UA patients (4.0 2.6) than in SA patients (2.7 1.6, P 0.01) and controls (2.1 0.8, P 0.001), but no significant difference existed between SA and controls (Fig. 1a).…”
Section: Comparison Of Neutrophil -Lymphocyte Ratio (Nlr) In Three Stsupporting
confidence: 81%
“…And the proportion of naïve T cells was ever used to reflect thymic output 48) . In addition, negative correlation between sj-TREC and NLR revealed that patients with higher NLR had more severe inflammatory status, more complex plaques 29,49) , and lower output of lymphocytes, such as T cells from the thymus. In this respect, this study high GS group was significantly lower than that of the low and intermediate GS groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these well-recognized predictors, neutrophil-to-lymphocyte ratio (NLR) has recently been recognized as a predictor of CAD severity assessed by the number of diseased vessels [10], the SYNTAX score [11,12], and the Gensini score [13,14]. However, there is a paucity of data validating the predictive value of NLR in assessing the severity of CAD specifically in NSTEMI patients.…”
Section: Introductionmentioning
confidence: 98%
“…Fakat literatüre bakıldığında hem AKS olgularda hem de stabil koroner arter hastalarında N/L oranı ve koroner arter hastalığı yaygınlığı arasında anlamlı ilişki olduğunu gösteren çalışmalar mevcuttur [23,24]. Chen ve arkadaşlarının yaptığı çalışmada 2976 stabil koroner arter hastası değerlendirilmiş, N/L oranının Gensini skoru ile belirlenen koroner arter hastalığı ciddiyetinin bağımsız prediktörü olduğu görülmüştür [25]. Benzer şekilde Tanındı ve arkadaşlarının yaptığı çalışmada, AKS olgular ve stabil anjina pektorisli olgularda, N/L oranı ve koroner arter hastalığı ciddiyeti(SYNTAX ve Gensini skoru ile belirlenen) arasında anlamlı korelasyon tespit etmişlerdir [26].…”
Section: Discussionunclassified